an open source for libraries collaboration (Chicago, 2002)
Introduction -- Open source software for libraries / Eric Lease Morgan -- Prospero / Eric Schnell -- Managing MARC with open source software -- Greenstone : collection management for digital works / Gordon W. Paynter ... [et al.] -- LTSP--Linus Terminal Server Project / Cindy Murdock.
Keywords: Open source software,Library catalogs; Automation